AUGMENTED REALITY STORY BOOK PROJECT â€œLegenda Asal Mula Barong Landungâ€ - Widiantara, Eka Putra; Darmawiguna, I Gede Mahendra; Crisnapati, Padma Nyoman; Sunarya, I Made Gede (Universitas Pendidikan Ganesha, 2014)
The objective of this research was using technology in developing the application as interactive and interesting media in introducing Jayapangus story. The application could attract the reader to read folktale especially folktale entitled Jayapangus.Â The research method was research and development for developing the application of Augmented Reality Story Book Jayapangus. In developing the application, the waterfall model until testing system step were used. This application used library vuforia which enabled to combine the visual object into the real object book and android smartphone to show three dimensions of story with the narration in this story book.Â The result of this research was a book which consisted of story and pictures of Jayapangus and Augmented Reality Story Book application based on android which enabled to show three dimensions of the story exactly on the pictures. It was completed with English narration. Therefore this application could be an attractive and interesting media to introduce and keep the culture.